A scoping review and evidence map of radiofrequency field exposure and genotoxicity: assessing in vivo, in vitro, and epidemiological data - Weller, Steven G.; McCredden, Julie E.; Leach, Victor; Chu, Cordia; Lam, Alfred King-yin (Frontiers in Public Health, 2025)
BackgroundStudies investigating genotoxic effects of radiofrequency electromagnetic field (RF-EMF) exposure (3 kHz−300 GHz) have used a wide variety of parameters, and results have been inconsistent. A systematic mapping of existing research is necessary to identify emerging patterns and to inform future research and policy.MethodsEvidence mapping was conducted using guidance from the Preferred Reporting Items for Systematic reviews and Meta-Analyses for Scoping Reviews (PRISMA-ScR). A comprehensive search strategy was applied across multiple research databases, using specific inclusion and exclusion criteria within each knowledge domain. Quantitative aggregation using tables, graphs and heat maps was used to synthesize data according to study type, organism type, exposure level and duration, biological markers (genotoxicity, cellular stress, apoptosis), RF-EMF signal characteristics, as well as funding source to further contextualize the evidence landscape. Quality criteria were applied as part of a focused analysis to explore potential biases and their effects on outcomes.ResultsOver 500 pertinent studies were identified, categorized as in vitro (53%), in vivo (37%), and epidemiological (10%), and grouped according to type of DNA damage, organism, intensity, duration, signal characteristics, biological markers and funding source. In vitro studies predominantly showed proportionally fewer significant effects, while in vivo and epidemiological studies showed more. DNA base damage studies showed the highest proportion of effects, as did studies using GSM talk-mode, pulsed signals and real-world devices. A complex relationship was identified between exposure intensity and duration, with duration emerging as a critical determinant of outcomes. A complex U-shaped dose-response relationship was evident, suggesting adaptive cellular responses, with increased free radical production as a plausible mechanism. Higher-quality studies showed fewer significant effects; however, the funding source had a stronger influence on outcomes than study quality. Over half (58%) of studies observing DNA damage used exposures below the International Commission of Non-Ionizing Radiation Protection (ICNIRP) limits.ConclusionThe collective evidence reveals that RF-EMF exposures may be genotoxic and could pose a cancer risk. Exposure duration and real-world signals are the most important factors influencing genotoxicity, warranting further focused research. To address potential genotoxic risks, these findings support the adoption of precautionary measures alongside existing thermal-based exposure guidelines.